Enhanced degradation of pretilachlor in soil and sediment slurries by inoculation of a mixed bacterial culture under anaerobic condition - Duc, Ha Danh; Gia Hien, Nguyen; Dieu Thuy, Nguyen Thi; Kim Xuan, Nguyen Thi (Academia Journal of Biology, 2025)
Pretilachlor is a main component of herbicides widely applied to control weeds, causing serious environmental problems. However, its degradation is so slow under anaerobic conditions. This study evaluated the enhancement of pretilachlor degradation using a mixed culture of Pseudomonas sp. Pr1, Proteiniclasticum sp. Pr2 and Paracoccus denitrificans Pr3. The result showed that the degradation using a horizontal-flow anaerobic immobilized biomass bioreactor gave a degradation rate of 3.11 ± 0.31 µM/day after six cycles. Moreover, the inoculation of these bacteria significantly augmented the degradation in slurries of soil collected from a paddy field and sediments from a river. In addition, the determination of pretilachlor degradation in water and soil collected from a paddy field showed that the degradation rates followed an order: a slurry of soil and water (20:80, w/w) > water ≈ soil and water (50:50, w/w). However, adjuvants in an herbicide significantly caused adverse effects on substrate degradation. This study showed the role of isolated bacteria in degradation augmentation in liquid media. It also provided information on the degradation differences in water soil slurry, and soil collected from a paddy field.